PROCESSING OF INDUSTRIAL IRON CONTAINING WASTES - S. L. Rovin; L. E. Rovin (Литьë и металлургия)
This article presents the technological process of direct production of iron-carbon alloys from dispersed iron containing wastes in rotary tilting furnace, which allows to exclude the preliminary preparation of initial raw material.